Contribution of the Mangrove ecosystem to the Gastropod community at Pantai Bahagia village, Muara Gembong, West Java - Dwijaya, Bayu Awifan; Krisnanti, Sukma Awifan; Ramdhani, Ardo (Genbinesia Journal of Biology, 2021)
The Mangrove ecosystem of Muara Gembong has been under continuing stress by land occupation, land conversion, and abrasion. This research was aimed to reveal the mangrove and gastropods community structure circumstance. A contribution of the environmental factor was also assessed to evaluate the interaction among them and to track the changes of the ecosystem. This research was conducted by purposive sampling in 3 sampling sites, these were a full reforestation site (A), a central site, that was exist by natural process (B), also a moderate reforestation site (C), with 3 sampling replication each site. About 4 mangrove species within shoreline has been progressively important as a protective flood barrier and abrasion at Muara Gembong. The highest gastropod diversity was found in the B1 site, while the highest dominance was found in A2. The C2 site is the only site that showed us a uniform dispersion of gastropods when the other sites showed a clumped dispersion. It can be implied that the ecosystem has been gradually degraded. Eigen and loading value from Canonical Correspondence Analysis (CCA) revealed that a gastropods community was holistically affected by pH, basal area, canopy, substrate, and TDS. The community of gastropods was influenced 62.14% by pH, and 34.29% by basal area. while the highest dominance was found in A2. The C2 site is the only site that showed us a uniform dispersion of gastropods when the other sites showed a clumped dispersion. It can be implied that the ecosystem has been gradually degraded.